Сучасні проблеми енергозбереження тракторів загального призначення - Лебедєв, Анатолій Тихонович; Шуляк, Михайло Леонідович; Рапута, Вадим Валерійович (Національний технічний університет "Харківський політехнічний інститут", 2022)
У статті за відомими публікаціями узагальнені результати досліджень по енергозбереженню тракторів загального призначення, що базуються на аналізі питомих тягових опорів сільськогосподарських машин, що агрегатуються з трактором. Аналізується відомий спосіб оцінки опору руху сільгоспмашин за прискоренням розгону трактора. Сформульована невирішена проблема енергозбереження тракторного агрегату з GPS у системі точного землеробства.

The article based on well-known publications summarizes the results of research on the energy saving of generalpurpose tractors, based on the analysis of the specific traction resistances of agricultural machines aggregated with the tractor. The well-known method of estimating the resistance to the movement of agricultural machines based on the acceleration of the tractor acceleration is analyzed. The unsolved problem of energy saving of the tractor unit with GPS in the precision farming system is formulated. The energy saving of the tractor is considered to be one of the most costeffective, for the assessment of which the various publications have suggested different methods. But they is not primed on the method of assigning specific work (on unit of work) to fuel consumption a tractor unit, even when we are has the information of elemental energy consumption. It is recommended to evaluate the energy consumption of the tractor during the technological process behind the traction resistance of the machines by the difference in the acceleration of the tractor acceleration.
Modern problems of energy saving of general purpose tractors
Keywords: трактор; сільгоспмашина; опір руху; енергозбереження; прискорення розгону; реєстраційний комплекс; точне землеробство; tractor; agricultural machine; movement resistance; energy saving; acceleration; registration complex; precision farming